Perbandingan Tingkat Maslahah Pengguna Jalan Pada Sistem Satu Arah di Kota Bogor - Maya Apriyana; Tuti Kurnia (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The purpose of this study is to determine the effect of one-way system on utility level of road users in Bogor city. The research method used is quantitative research methode, with data collection technique that is by free interview and distribution of koesioner to public of road user and driver of public transportation. Analytical tool used is IPA (Importance Performance Analysis).  The result obtained from the interview stated that the one –way system is more jammed, the distance becomes more distant, the income of public transport drivers becomes more reduced and the increase in fuel consumption, while the result of the IPA state that public and public transport drivers more satisfied before the system one goog directions in mileage, location access, in fuel consumption. After the one-way system of public and drivers are more satisfied with the arrangement of bogor city becomes more organized that before the one way system. The benefit of this one way policyof the system does not provide enough meaning to the road users as a whole.